Interfacing of Supernaturalism and Religious Sensibilities: A Stylistic Analysis of S.T Coleridge’s “The Rime of the Ancient Mariner” - Khan, Muhammad Ali; Awan, Nazakat (Pakistan Languages and Humanities Review, 2022)
Samuel Taylor Coleridge, the leading poet of British romanticism, is reputed as one of the creators of supernaturalism. This article aims to analyze S.T Coleridge’s poem “The Rime of the Ancient Mariner” from a stylistic point of view. The analysis is made under the aspects of semantic, grammatical, lexical, graphilogical and syntactic patterns. This stylistic analysis is helpful in understanding the basic and biblical concepts of the poem along with the ability to examine how supernaturalism creates a religious sensibility. Furthermore it also highlights the lexical items which are used by the poet in un-customized or abnormal way to create a difference between the literary language that is used in poetic context and ordinary language used in daily life. The stylistic approach also depicts the variation in style and the impact of this variation on the mind of the readers. It also helps to examine various aspect of style like the structure, grammar, meaning and form. Style is generally dependant on linguistic level. it can be defined as the appropriate use of words or language in a sentence and it varies from text to text.